KEBIJAKAN HUKUM PIDANA TERKAIT SANKSI PIDANA BAGI PELAKU KEJAHATAN SIBER DI INDONESIA - Panggabean, Enjelina; Jamba, Padrisan (SCIENTIA JOURNAL, 2025)
A new challenge for law enforcement in the digital era, including in Indonesia, is cybercrime. This abstract discusses the criminal policy implemented to address cybercrime, with a particular emphasis on regulations, enforcement, and the issues faced. In recent years, Indonesia has adopted the ITE Law (Information and Electronic Transactions Law) to regulate behavior in cyberspace. However, the implementation of this policy often encounters obstacles such as a lack of trained human resources, insufficient public awareness of cyber laws, and technical issues in investigating cybercrime cases. The introduction, main section, and conclusion of the literature reviewed in this research are discussed. The data sources for this section come from relevant books, scholarly articles, or journals.Make recommendations on how to strengthen the legal framework, enhance inter-agency cooperation, and educate the public on creating a safer digital environment. With these efforts, it is hoped that criminal policies in Indonesia can be more effective in preventing and addressing cybercrime.